2004
DOI: 10.1191/1740774504cn003oa
|View full text |Cite
|
Sign up to set email alerts
|

Reported use of data monitoring committees in the main published reports of randomized controlled trials: a cross-sectional study

Abstract: In 2000, about a quarter of main RCT reports mention use of a DMC. Actual use of DMCs is likely to be somewhat greater. Reporting use of a DMC was more likely for larger and longer trials among other factors. We believe the factors affecting reported use affect actual use. It is recommended that when a DMC oversees a trial, brief details should be explicitly included in the main trial paper. Standard nomenclature for DMCs is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 11 publications
4
44
1
2
Order By: Relevance
“…We found results similar to Chan et al, including a lower reporting rate of interim analyses in publications (26%) than in protocols (35%). Similar to Sydes et al, we found a positive association of DSMB presence with multicenter study design, larger sample size, and trials including a placebo arm [20]. In addition, we showed that these trial characteristics were also associated with the use of interim analyses.…”
Section: Comparison With Other Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…We found results similar to Chan et al, including a lower reporting rate of interim analyses in publications (26%) than in protocols (35%). Similar to Sydes et al, we found a positive association of DSMB presence with multicenter study design, larger sample size, and trials including a placebo arm [20]. In addition, we showed that these trial characteristics were also associated with the use of interim analyses.…”
Section: Comparison With Other Studiessupporting
confidence: 88%
“…Most previous research addressing the use of interim analyses, stopping rules, and DSMBs has been based on data from RCT publications without taking into account whether trials were discontinued or completed [6,7,[20][21][22]. One exception, a study by Chan et al comparing 70 protocols approved by a REC in Denmark with corresponding publications [23], reported that 13 (18%) mentioned interim analyses in protocols, but only 5 (7%) were mentioned in corresponding publications [23].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Der publizierte Vorschlag für eine Charta umfasst insgesamt 10 Unterpunkte, die präzise vom Sponsor beschrieben werden sollen [9]. Neben einem berichteten Anstieg von DMCs in randomisierten, kontrollierten klinischen Prüfungen über das letzte Jahrzehnt konnten Regressionsmodelle in der Auswertung der Literatur angewandte Kriterien für einen Einsatz von DMCs aufzeigen: Mortalitätsend-punkte, multizentrische klinische Prü-fungen, Anzahl der Prüfungsteilnehmer und Placebokontrolle [10,11].…”
Section: Data Monitoring Committees Third Pillar In the Methodical Cunclassified
“…Looking at the contents of the first issue, one sees what that meant: a lively and eclectic collection of articles and commentaries that still inform and entertain, every one written by someone in the SCT or a colleague. There was a mix of methodology; one on dynamic treatment regimens by Lavori and Dawson [1], three on data monitoring committees, two from the DAMO-CLES group (Data Monitoring Committees: Lessons, Ethics, Statistics) [2][3][4], a delightful retrospective and accompanying editorial on the Salk polio vaccine trial [5,6], and a very nice article on the groundbreaking model of 'coverage under evidence development' embodied by the National Emphysema Treatment Trial [7], followed by four terrific commentaries. But my favorite, 10 years later, was a profile of a founding SCT member, Paul Meier [8], by my colleague and erstwhile associate editor Harry Marks [9], neither of whom survived the ensuing decade.…”
Section: Steven N Goodmanmentioning
confidence: 99%